A developed method to measure and calculate the solar albedo of discrete-particle layers. (December 2019) - Wang, Jiwei; Zhang, Mingyi; You, Zhilang; Pei, Wansheng; Bai, Ruiqiang
Highlights: A method was developed to measure the solar albedo of rough surface layers with large particle sizes. The albedo of rough surface layers was theoretically studied by the discrete-particle model. The albedo of rough surface layers was mainly affected by solar conditions and particle properties. The methods could be used to measure and calculate the albedo of crushed-rock layers or gravel piles. Abstract: Albedo is an important parameter for many research fields, including solar energy, building energy conservation, road engineering, regional and global climate, environmental protection, and other fields. The solar albedo of rough surface is always lower than the reflectance of homogeneous and flat surface due to the irregular and nonuniform surface properties. It is difficult to determine the solar albedo of rough surface in laboratory, especially for the surface with large particle sizes or cavities. Here a method was developed to measure the solar albedo of rough surface layers based on discrete-particle model in consideration of particle sizes, diurnal variations, and solar and season conditions. Besides, the solar albedo was theoretically studied by the discrete-particle model with and without cavities, which shows good performance. The relationship between the solar albedo of rough surface and the reflectance of flat surface was also studied. This developed methods can be applied to many engineering fields, such as the crushed-rock layers of embankments in permafrost regions and the cool roofing of buildings in tropical regions. The results also showed that the rough surfaces with higher reflective coatings can increase the solar albedo with greater values, which may be expected to raise the cooling performance of above engineering applications.